2018
DOI: 10.1038/aps.2017.195
|View full text |Cite
|
Sign up to set email alerts
|

Phoenixin: a novel brain-gut-skin peptide with multiple bioactivity

Abstract: In this brief review we summarize the current fndings relative to the discovery of a small peptide ligand, phoenixin (PNX). Using a bioinformatic approach, two novel peptides PNX-14 and PNX-20 containing 14 and 20 amino acids, respectively, were isolated from diverse tissues including the brain, heart, lung and stomach. Mass spectrometry analysis identified a major and minor peak corresponding to PNX-14 and PNX-20, in rat or mouse spinal cord extracts. With the use of a rabbit polyclonal antiserum, phoenixin i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…A recent study showed that PNX was also expressed on the mammalian heart and served as a cardioprotective factor. Although it consisted of 20 amino acids, PNX was shown to reduce the contractility and relaxation of heart in vitro test, and it could inhibit apoptosis to narrow the infarct size and accelerate the recovery of contractility compared with the ischemia/reperfusion (I/R) treat alone [83,84], In addition, the experiments on the heart of obese rats showed the same result. All these evidences suggested that PNX was a novel regulating small molecule to exert in both the heart and metabolic disorders.…”
Section: New Frontier Of Bsms As New Clinical Application In Cvdmentioning
confidence: 91%
“…A recent study showed that PNX was also expressed on the mammalian heart and served as a cardioprotective factor. Although it consisted of 20 amino acids, PNX was shown to reduce the contractility and relaxation of heart in vitro test, and it could inhibit apoptosis to narrow the infarct size and accelerate the recovery of contractility compared with the ischemia/reperfusion (I/R) treat alone [83,84], In addition, the experiments on the heart of obese rats showed the same result. All these evidences suggested that PNX was a novel regulating small molecule to exert in both the heart and metabolic disorders.…”
Section: New Frontier Of Bsms As New Clinical Application In Cvdmentioning
confidence: 91%
“…In rat brain, nesfatin-1 showed a high degree of co-localization with phoenixin. Nearly one-fifth of cells in the PVN, Arc, ventromedial nucleus and lateral hypothalamic nucleus showed irPNX ( Lyu, et al, 2013 ; Lyu et al, 2018 ). Bioinformatic survey demonstrated that both phoenixin and nesfatin were as ancient neuropeptides with premetazoan origin ( Yanez-Guerra et al, 2022 ).…”
Section: Interaction With Nesfatin-1mentioning
confidence: 99%
“…Moreover, the correlation between the increased plasma levels of PNX, LH, and androgen hormones suggests a possible role for the peptide in the development of human polycystic ovary syndrome (PCOS) . Even if additional physiological activity of PNX are known, such as in food intake control, the cardiovascular system, and in skin, the predominant idea is that PNX plays a crucial role in the modulation of the HPG axis with a significant relapse in reproduction, that may be potentially useful in translational medicine.…”
Section: Introductionmentioning
confidence: 99%